Perbedaan hasil belajar matematika siswa yang diajar dengan menggunakan metode drill dan ekspositori - Ellisia Kumalasari (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2016)
The aim of the study was to obtain data and empirical information about the differences in students’ mathematics learning outcomes in grade-XI who were taught by drill and expository method. The samples were chosen by simple random sampling technique to be grouped into experiment and control class, each class consisted of 30 students. The experiment class was treated by drill method and the control class by the expository method. Thirty multiple choices were used as the instruments. The test of validity and reliability of the instrument stated that the instruments were fit for use. Based on the data analysis by t-test, it was concluded that there were differences between mathematics learning outcomes of students who was treated by drill method and expository method. The result of this research showed that mathematics learning outcomes of students who was treated by drill method were higher than expository method.